Leaf-like copper-based nanocomposites as adsorbents for dispersive solid-phase extraction: application to determination of cobalt in lemon balm tea using FAAS - Yazici, Elif; Ayyildiz, Merve Firat; Bodur, Sueleyman; Bakirdere, Sezgin (SPRINGER, 2025)
This study proposed an analytical method named dispersive solid phase extraction-flame atomic absorption spectrometry (DSPE-FAAS) for the quantitation of cobalt in balm tea samples. Copper-based nanocomposites were used as adsorbent in the DSPE process. Influential DSPE parameters such as pH/volume of buffer solution, nanocomposite amount, sample volume, mixing type/period, and eluent concentration/volume were optimized to augment signal-to-noise ratio of cobalt. System analytical performance study for the DSPE-FAAS method was carried out, and limit of detection/quantitation (LOD/LOQ) values were recorded as 5.80 mu g/kg and 19.33 mu g/kg, with a relatively wide dynamic range (20.59 - 400.68 mu g/kg). Spiked lemon balm tea samples were employed to perform recovery studies, and satisfactory recovery results were obtained between 76.7% and 128.1% via the external standard calibration method. According to the recorded recovery results, the proposed DSPE-FAAS method can be accurately applied to lemon balm tea samples in order to determine cobalt content.
Keywords: Cobalt; Dispersive solid phase extraction; Flame atomic absorption spectrometry; Leaf-like copper-based nanocomposites; Lemon balm tea; Health effects; WATER SAMPLES; NANOPARTICLES; NICKEL; OXIDE; NANORODS; IONS; PRECONCENTRATION; MICROEXTRACTION; SPECTROMETRY; ADSORPTION; Chemistry; Science & Technology - Other Topics; Materials Science